Experimental Study on the Effect of Offset Notch on Fracture Properties of Rock under Three-Point Bending Beam. (8th February 2020) - Guo, Qifeng; Wu, Xinghui; Cai, Meifeng; Miao, Shengjun
Abstract : To investigate the effects of offset notch on the fracture properties of rock beam under bending load, granite beam specimens with "one single offset notch" and "central and offset double notches" are made. A series of three-point bending beam tests on the specimens are carried out by controlling the displacement rate of central notch. The whole load-displacement (P-CMOD) curves are obtained. Experimental results show that the larger the distance between the offset notch and beam central is, the larger are the peak load and nominal strength of the specimen. The peak load and nominal strength for the "central and offset double notches" specimens are both larger than those for the "single central notch" specimen. A fracture model considering the effect of offset notch is developed, and the relationship between the offset notch parameter, tensile strength, and fracture toughness is established.